Mitrula aurea sp. nov., A New Aero-Aquatic Species from the Republic of Korea. Issue 4 (4th July 2022) - Cho, Sung-Eun; Kim, Hyung So; Kwag, Young-Nam; Lee, Dong-Hyeon; Han, Jae-Gu; Kim, Chang Sun
Abstract: The genus Mitrula (Mitrulaceae, Helotiales), as also known as swamp beacons, inhabits submerged, decaying vegetation in standing or decaying needles, twigs, leaves, and shallow water. They play an important role in carbon cycling in some freshwater ecosystems. In the herbarium of the Korea National Arboretum (KH), seven Mitrula specimens were collected during mushroom forays in the period from 2019 to 2021. The Korean collections were found to be macromorphologically closely related to M. paludosa and M. elegans, but micromorphologically they could be distinguished by characteristics of slightly narrower asci and aseptate ascospores. Our molecular phylogenetic analyses of the internal transcribed spacer (ITS) and 28S rDNA regions also revealed that our specimens were related to M. paludosa and M. elegans, but formed a distinct clade. Based on these results, we reported our specimens as new to science and discussed the phylogeny and diversity of Mitrula species.